Mycotoxins in Animal Products Milk and Milk Products, and Meat - Weidenbörner, Martin (Springer International Publishing : Imprint: Springer, 2019)
This book is one of three volumes expanding upon content found in Mycotoxins in Foodstuffs, Second Edition, and focuses on milk and milk products, and meat. Foodstuffs of plant origin that play only a minor role in mycotoxin contamination, such as asparagus, are also covered. Mycotoxins in Animal Products - Milk and Milk Products, and Meat comprises: More than 100 new publications and 300 publications in all Single chapter overview with all mycotoxins and each foodstuff that is contaminated Coverage of "co-contamination," showing the co-occurrence of mycotoxins in a foodstuff, where possible Coverage of "further contamination," describing further foodstuffs with their mycotoxins documented, where possible List of articles dealing with conventionally and organically produced foodstuffs and their mycotoxin contamination .